2020
DOI: 10.1021/acsaelm.0c00013
|View full text |Cite
|
Sign up to set email alerts
|

Excess Random Laser Action in Memories for Hybrid Optical/Electric Logic

Abstract: To surmount the scalability limitations of the nanoelectronics industry, the invention of resistance random access memory (RRAM) has drawn considerable attention in recent years for being a new-era memory. Nevertheless, the data transmission speed of RRAM is confined by virtue of its sequential reading nature. To improve upon this weakness, a hybrid optical/electric memory with I ON/I OFF ratio up to 105 and laser-level optical signal is proposed. The device was engineered through an adroit design of integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A relevant RRAM device is conductive-bridging random access memory (CBRAM), which has a high potentiality to fulfil the necessities for next-generation nonvolatile memory (NVM) technology. Yu-Ting Cheng et al 72 reported silver NPs (scattering centers) agglomeration and form metal filaments via electrochemical metallization (ECM) process 180 in the insulating layer. The insulating layer is composed of PMMA and CdSe/ZnS colloidal core−shell QDs during the ON/OFF switching process.…”
Section: Applicationsmentioning
confidence: 99%
“…A relevant RRAM device is conductive-bridging random access memory (CBRAM), which has a high potentiality to fulfil the necessities for next-generation nonvolatile memory (NVM) technology. Yu-Ting Cheng et al 72 reported silver NPs (scattering centers) agglomeration and form metal filaments via electrochemical metallization (ECM) process 180 in the insulating layer. The insulating layer is composed of PMMA and CdSe/ZnS colloidal core−shell QDs during the ON/OFF switching process.…”
Section: Applicationsmentioning
confidence: 99%
“…require high-density storage devices to store and read the data requested in the application. , Silicon-based “flash” memory is undoubtedly the most successful nonvolatile memory at present, but people’s demand for storage density continues to increase, and the miniaturization of devices is becoming increasingly difficult. The size of the device is approaching the physical limit, so it is necessary to develop a new type of nonvolatile memory with high performance and low power consumption. Resistive random access memory (RRAM) has attracted widespread attention in recent years because of its fast read and write speed, simple structure, and low power consumption. It can store data by not only the high resistance state (HRS) and the low resistance state (LRS) but also the intermediate states between HRS and LRS; furthermore, RRAM can also be used for other functions, such as multilevel data storage and simulation of biological synapses. A variety of materials have been reported to exhibit memory behavior, such as metal oxides, organic polymers, perovskite materials, and so on. With the development of technology, researchers are devoting more attention to some aspects of the device performance, such as pollution-free, low power consumption, recyclable regeneration, and high-density storage .…”
mentioning
confidence: 99%